The Impact of University Presentation on Quality and Quantity of Students: The Case of Azerbaijani Students - Aliyeva, Leyla; Aliyev, Vasif (International Review of Management and Marketing, 2025)
In the last decade, Azerbaijan has seen the establishment of numerous higher education institutions. These newly founded universities aim to fulfill two primary goals: Ensuring the quality of education for students and attracting enough students to maintain institutional viability. This study analyzes the factors that influence students’ university preferences and evaluates the effectiveness of university promotional activities. The research assesses the concept of service in relation to universities in Azerbaijan and examines the impact of promotional activities through a survey. The study sample consists of 243 students enrolled in various departments across three universities (two public and one private), established at different times and differing in quality and facilities. The sample includes 185 female students (76.1%) and 58 male students (23.9%), with 134 students (55.1%) on full or partial scholarships and 109 students (44.9%) without scholarships. Geographically, 141 students (58%) are from Baku, 88 (14%) from other regions, 12 (4.9%) from Sumgait, and 2 (0.8%) from Ganja. The universities represented include Khazar University (119 students, 49%), Pedagogical University (66 students, 27.2%), and Economics University (57 students, 23.5%). A survey was developed and administered to these students, with responses analyzed using reliability analysis and t-tests. The study’s results revealed that Hypothesis 6, which posited that tuition fees and scholarship opportunities influence university choice, showed a statistically significant difference. Other hypotheses were not validated. Based on these findings, it is recommended that universities focus on improving service quality and student satisfaction to remain competitive. Future studies could include final-year students from additional faculties to broaden the scope of the findings.